DOI: 10.2969/aspm/08310019
|View full text |Cite
|
Sign up to set email alerts
|

A brief survey of FJRW theory

Abstract: In this paper we describe some of the constructions of FJRW theory. We also briefly describe its relation to Saito-Givental theory via Landau-Ginzburg mirror symmetry and its relation to Gromov-Witten theory via the Landau-Ginzburg/Calabi-Yau correspondence. We conclude with a discussion of some of the recent results in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…These authors have also shown that the FJRW invariants contain the same information as the Gromov-Witten invariants, as is expected from by Landau-Ginzburg/Calabi-Yau correspondence [9]. For reviews of FJRW theory see also [70,71].…”
Section: Fjrw Theorymentioning
confidence: 74%
See 1 more Smart Citation
“…These authors have also shown that the FJRW invariants contain the same information as the Gromov-Witten invariants, as is expected from by Landau-Ginzburg/Calabi-Yau correspondence [9]. For reviews of FJRW theory see also [70,71].…”
Section: Fjrw Theorymentioning
confidence: 74%
“…It satisfies certain key properties and axioms such that the set of correlations functions defines a cohomological field theory, called FJRW theory, in the sense of Kontsevich and Manin [77] (cf. also [71]), on the space H FJRW (W, G) of chiral primary fields of the Landau-Ginzburg orbifold (W, G). FJRW theory is then intersection theory on W g,n (W, G), generalizing the case of topological gravity [74].…”
Section: A Brief Guide To Fjrw Theorymentioning
confidence: 99%
“…This definition is the standard definition of diagonal symmetries (see, e.g., [17]). Note that G diag W can be viewed as a subgroup of G max W via diagonal matrices.…”
Section: Maximal Symmetry Groupmentioning
confidence: 99%
“…While the state spaces have similar definitions, the grading and product structures are very differentfor example, the multiplicative identity on the B-side lies in the untwisted sector, whereas the multiplicative identity on the A-side lies in the sector indexed by j W . We won't discuss the product structure any further here, but the interested reader can find the definition of the B-model multiplication in [2] or [20], and the definition of the A-model product in [14] or [17], when G and G * are groups of diagonal symmetries. When G and G * are not diagonal, the B-model product has not yet been defined, as far as we know, whereas the A-model structure comes from invariants of the associated Gauged Linear Sigma Model (see, e.g., [15], though we are unaware of the invariants having been computed for any examples).…”
Section: The B-model State Spacementioning
confidence: 99%
See 1 more Smart Citation